Mixosauridae Baur 1887 - Roberts, Aubrey Jane; Engelschiøn, Victoria Sjøholt; Hurum, Jørn Harald (Zenodo, 2022)
Family Mixosauridae Baur, 1887 Type genus : Mixosaurus Baur, 1887. Included genera : Mixosaurus Baur, 1887 and Phalarodon Merriam, 1910. Diagnosis .—Modified from Liu et al. (2013). Mixosauridae can be differentiated from other ichthyosaurs by the following combination of characters: premaxilla pointed posteriorly and lacking subnarial and supranarial processes; long sagittal crest which reaches the nasal; large anterior terrace of the upper temporal fenestra which reaches the nasal; pubis is significantly larger than the ischium; narrow and high caudal neural spines; large mid-caudal vertebral centra; heterodonty, posterior teeth more robust than anterior teeth; a pronounced notch present between the deltopectoral crest and the humeral head; distal carpal 1 larger than other carpals; three flattened middle metacarpals which are short and only have a slightly constricted shaft. Published as part of Roberts, Aubrey Jane, Engelschiøn, Victoria Sjøholt & Hurum, Jørn Harald, 2022, First three-dimensional skull of the Middle Triassic mixosaurid ichthyosaur Phalarodon fraasi from Svalbard, Norway, pp. 51-62 in Acta Palaeontologica Polonica 67 (1) on page 54, DOI:10.4202/app.00915.2021, http://zenodo.org/record/10981077